Innovation in Islamic Education at the Majelis Taklim An-Nisa, Jatirasa Village, Bekasi City - Hidayat, Ajat; Kosim, Muhammad; Yafi, Salman (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2024)
This article seeks to delineate the changes implemented by the Majelis Taklim An-Nisa in response to contemporary events. while disclosing numerous initiatives aimed toward progress. The employed methodology is qualitative, utilizing a case study technique. The data source was obtained via interviews with 10 informants, including 1 chairman and 9 members of the An-Nisa Taklim Council. Informants were selected through a purposive sampling method based on the following criteria: (1) possessing a comprehensive understanding, (2) having available time, (3) maintaining active status, and (4) being capable of articulating facts accurately. The researcher conducted observations and documentation to enhance the research data. The acquired data was subsequently analyzed through data reduction, data presentation, and the formulation of study conclusions. The data validation methodology entails verifying the data through several sources, methodologies, and temporal contexts. The research findings demonstrate that the Majelis Taklim An-Nisa provides explicit learning references, essential educational materials, and employs technology to mitigate encountered challenges. The researchers anticipate that the findings of this study will catalyze other taklim assemblies to enhance the quality of learning in various dimensions.